Pengaruh Interaksi Siswa dan Guru dalam Pembelajaran Seni Teater Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri 6 Tebo - Fingki Novi Arsita; Indrayuda Indrayuda (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The purpose of this study was to determine the effect of the interaction between drama students and teachers on the academic achievement of class VIII students of SMP Negeri 6 Tebo. The type of research used in this study is a mixed method that combines quantitative and qualitative research. In this research, the sampling technique used purposive sampling method with a sample of 30 students in this study. Data collection techniques used in this study were observation, questionnaires, interviews, and documentation. The data analysis technique in this study is simple linear regression. The results of the study prove that theater arts for class VIII 1 of Tebo 6 Public Middle School with the theme Tasainen for the 2022/2023 school year have a significant positive effect on student-teacher interaction abilities and student learning outcomes. If Fcount 9.71 > 4.20 then H0 is rejected, with a significance level of 0.004 and 0.05, it can be concluded that student-teacher interaction has a significant effect on academic achievement in theatre. From the results of the coefficient R2 (R-squared) obtained with a coefficient of 0.231, it can be concluded that the effect of student-teacher interaction is 23.1% in the theater arts subject at SMP Negeri 6 Tebo. While the rest are other effects such as internal factors in the form of physical factors and psychological factors, as well as external factors in the form of family factors, school factors, and community factors.